UJI DAYA TARIK PAKAN HAMA TIKUS TERHADAP RODENTISIDA ALAMI YANG MENGANDUNG UMBI GADUNG (Dioscorea hispida) - Indriani Indriani; Tuti Heiriyani; Riza Adrianoor Saputra (Universitas Lambung Mangkurat, 2021)
In an effort to cope with rat pest attacks, most farmers control chemically which is bad for living creatures and leaves residues for the environment. One of the recommended controls is to use natural rodenticides derived from harmless and environmentally friendly gadung tubers. This study aims to determine the effect of the interaction of the basic ingredients of the type of flour with some concentration of the gadung tuber solution to the appeal of white mouse feed. This research was conducted from April to May 2018 at the Laboratory of Agroecotechnology Department of Agricultural Faculty of Lambung Mangkurat University Banjarbaru. The experimental design used was Randomized Block Design of two factors, the first factor was flour base (B) and the second factor was the concentration of the gadung tuber solution (G). The results showed that there was no interaction between flour base material and concentration of gadung tuber solution, but it had a significant effect on single factor that is concentration of tuber bulb solution on all observation variables. The concentration of the best gadung bulb solution in influencing the observed variables of feed consumption, the percentage of death and the time of death of white mice is g1 (30% concentration of the gadung tuber solution), where in the treatment the feed consumed by white mice is 30% from the total feed given, and capable of killing 100% white mice with the fastest death time of 13 days.